1991
DOI: 10.1071/rd9910051
|View full text |Cite
|
Sign up to set email alerts
|

Composition of uterine flushings from Large White and prolific Chinese Meishan gilts

Abstract: This study examined differences in selected components of uterine secretions from Large White and prolific Chinese Meishan gilts during the oestrous cycle or early pregnancy. Total recoverable protein, uteroferrin (measured as acid phosphatase activity), acyl aminopeptidase, calcium, sodium, potassium, immunoglobulins A and G, glucose, fructose, oestradiol-17 beta, and prostaglandins F2 alpha (PGF2 alpha) and E2 (PGE2) in uterine flushings were measured. During the oestrous cycle, breed effects were detected o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
1
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 23 publications
0
24
1
1
Order By: Relevance
“…Therefore, stimulation of intra-uterine PGE 2 secretion could contribute to the inhibition of immune rejection of the embryo and to the increased survival of the embryo. In fact, uterine secretions of Meishan sows, known to have low embryonic mortality, contain three times more PGE 2 than those of Large White sows (Bazer et al 1991). Therefore, folic acid could act on embryonic survival, at least partially, by stimulating the immuno-protective activity of the uterus.…”
mentioning
confidence: 99%
“…Therefore, stimulation of intra-uterine PGE 2 secretion could contribute to the inhibition of immune rejection of the embryo and to the increased survival of the embryo. In fact, uterine secretions of Meishan sows, known to have low embryonic mortality, contain three times more PGE 2 than those of Large White sows (Bazer et al 1991). Therefore, folic acid could act on embryonic survival, at least partially, by stimulating the immuno-protective activity of the uterus.…”
mentioning
confidence: 99%
“…Although FGF7 is a unique SC-derived paracrine mediator of hormone-regulated epithelial growth and differentiation, the uterine luminal epithelium of the pig is unique in its expression of FGF7 in response to E2 with P4 being permissive to effects of E2 [62]. FGF7 binds to and activates FGFR2IIIb expressed by uterine epithelia and conceptus trophectoderm to increase cell proliferation, phosphorylated FGFR2IIIb, the MAPK cascade and expression of urokinase-typeplasminogen activator (PLAU), a marker for trophectoderm cell differentiation.From about Day 20 of pregnancy, FGF7 is expressed by uterine GE in response to P4 and is presumed to continue to affect uterine epithelia and conceptus development in pigs [63,64]. Indeed, P4 has profound effects on the expression of genes in pig uterine epithelia, particularly in the GE.…”
mentioning
confidence: 99%
“…Breed (Legault and Caritez, 1983;Bolet et al, 1986). This appears to be largely due to an altered embryonic growth and improved embryonic development and survival (Bazer et al, 1988(Bazer et al, , 1991Simmen et al, 1989;Wilmut et al, 1992;Anderson et al, 1993), although additional alterations of ovulation rate have been identified in some studies (Ashworth et al, 1992, Haley andLee, 1993). However, the mechanisms involved in these differences have not been fully clarified.…”
mentioning
confidence: 99%
“…This appears to be largely due to an altered embryonic growth and improved embryonic development and survival (Bazer et al, 1988(Bazer et al, , 1991 Simmen et al, 1989;Wilmut et al, 1992;Anderson et al, 1993) Immunostaining was performed according to the method described by Meduri et al (1996). This method is based on the formation of a streptavidin-biotin complex using the Vectastain ABC kit (Vector Laboratory, Burlingame, CA).…”
mentioning
confidence: 99%